Producto de la comisión mixta de las AFP y su incidencia en la situación económica y financiera de los empleadores y potencial humano. - Arteaga Chanduví, Flor Milagros (2014)
The present research has as main objective to demonstrate how the Joint Commission of the AFP affects the Economic and Financial Employers and Manpower Situation, as this new commission was created by the Reform of Private Pension System - Law 29903. The research was analytical - descriptive, to develop it surveyed 140 members of the AFP which reside in the city of Trujillo, and also has Forms of Remuneration in the months May and June 2013 in which the earlier sample and after making the decision affiliate commission while an interview was conducted at Prima AFP officer who gave us more information about the Joint Commission and all that goes with the Reformation. When members polls showed ignorance and confusion about the new joint committee, if it suited them to her pension, moreover some members were not aware that they are currently providing commission. Verifying the forms shown increased availability of compensation in June compared to the month of May, and is due to the lower percentage charged by the joint committee to compare the fee flow. In the interview clarified that the pension will depend largely on the return earned by the investments made by the AFP. It is concluded that the general level of the AFP Joint Commission affects the economic and financial situation of employers and workers because the first one affects both become temporary retaining of such contributions and for workers because it represents a deduction weather becoming a fund used to cover social projections.